The Influence of Brand Awareness and Product Quality on Consumer Purchasing Decisions at Nuju Coffee Bandar Lampung : (Study on Students of the Faculty of Economics and Business University of Bandar Lampung) - Oktaviani, Miranda; Andala Rama Putra Barusman (The Es Economics and Entrepreneurship, 2025)
This study aims to analyze the influence of Electronic Word of Mouth (E-WOM), product quality, price, and store atmosphere on purchasing decisions through brand equity among Nuju Coffee consumers in Bandar Lampung. A quantitative approach is used in this study with the Partial Least Square-Structural Equation Modeling method (PLS-SEM). Data were collected through questionnaires from 280 respondents selected using purposive sampling from the population of students at the Faculty of Economics and Business, University of Bandar Lampung. The research results show that E-WOM, product quality, and store atmosphere significantly influence brand equity, while price does not have a significant impact. Brand equity also proves to have a significant effect on purchase decisions. Indirectly, E-WOM, product quality, and store atmosphere influence purchase decisions through brand equity, while price does not have an impact through this pathway. This research provides strategic recommendations for Nuju Coffee to enhance consumer experience through the optimization of brand equity and relevant dimensions such as E-WOM and store atmosphere.